Press influence over a soccer player image construction. Case study of Paolo Guerrero - Castaños Sarmiento, María Milagros (2019)
This research has a double purpose: on the one hand, to investigate and analyze the construction of the image of Paolo Guerrero, current cap- tain of the Peruvian National Soccer Team, through the journalistic discourse of the sports press (Depor and El Bocón) during the process of the Russia 2018 Qualifiers. And, on the other, the influence of this media construction on Peruvian fans. For this, three representative parties were taken as an ex- ample in which the Peruvian striker manages to score (Chile, Argentina and Colombia). What we try to demonstrate in this work, is what have been the discursive resources to inform about the goals of Paolo Guerrero and thus, hand in hand, how these covers and articles have influenced the population to create a positive image of the player. It is projected that the sports discourse of the written press has contributed positively to the construction of the public image of the soccer player.